ANALYSIS OF DISCOURSE MARKERS USED IN WRITING AT FIFTH SEMESTER STUDENTS OF ENGLISH EDUCATION SECTION IN IAIN BUKITTINGGI: - Melisa Renosari (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
This research was due to several problems found in the field; some students did not use discourse markers in writing to connect ideas. They said that they understood the lecturer's explanation about discourse markers, but they were difficult to use in the text. They had difficulty finding the appropriate discourse marker to use in the text. This study aimed to find out the kind of discourse marker students used in writing and the problems students had in using discourse markers. This research used descriptive quantitative as the research method. This study's population was 121 students in the fifth semester of the English language study program at IAIN Bukittinggi and used random sampling as a research sampling technique. The sample in this research was 24 students. In addition, data analysis was done by analyzing data, percentages and making conclusions. The researcher found some discourse markers used by students, 75% students using an elaborative marker, 64% students using an adversative marker, and 62,5% students using the causal inferential marker. Then, there were fourth problems students faced when using discourse markers. The problem was overused, non-equivalent exchange, mistranslation, misinterpreted relation.